2016
DOI: 10.1186/s13071-016-1860-3
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of chemically diverse compounds targeting the Plasmodium falciparum coenzyme A synthesis pathway

Abstract: BackgroundIn the fight against malaria, the discovery of chemical compounds with a novel mode of action and/or chemistry distinct from currently used drugs is vital to counteract the parasite’s known ability to develop drug resistance. Another desirable aspect is efficacy against gametocytes, the sexual developmental stage of the parasite which enables the transmission through Anopheles vectors. Using a chemical rescue approach, we previously identified compounds targeting Plasmodium falciparum coenzyme A (CoA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…Many potential inhibitors that interfere with the CoA biosynthetic pathway in Plasmodium have been reported ( Fletcher and Avery, 2014 ; Fletcher et al., 2016 ; Weidner et al., 2017 ). Although pantothenate analogs such as pantothenol (PanOH), CJ-15,801 ( Saliba and Kirk, 2005 ; Saliba et al., 2005 ; Spry et al., 2005 ), N5-trz-C1-Pan, and N -PE-αMe-PanAm ( Macuamule et al., 2015 ; Howieson et al., 2016 ) were expected to target PanK, they appeared to inhibit other enzymes than PanK.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many potential inhibitors that interfere with the CoA biosynthetic pathway in Plasmodium have been reported ( Fletcher and Avery, 2014 ; Fletcher et al., 2016 ; Weidner et al., 2017 ). Although pantothenate analogs such as pantothenol (PanOH), CJ-15,801 ( Saliba and Kirk, 2005 ; Saliba et al., 2005 ; Spry et al., 2005 ), N5-trz-C1-Pan, and N -PE-αMe-PanAm ( Macuamule et al., 2015 ; Howieson et al., 2016 ) were expected to target PanK, they appeared to inhibit other enzymes than PanK.…”
Section: Discussionmentioning
confidence: 99%
“…Coenzyme A (CoA) is an essential cofactor in many metabolic processes, involving more than 9% of approximately 3,500 cellular activities ( ). CoA biosynthesis has been attracting attention as a promising drug target ( Fletcher et al., 2016 ). In P. falciparum , CoA is generated by four enzymatic reactions initiated by the conversion of pantothenate (Vitamin B5) to 4-phosphopantothenate, catalyzed by pantothenate kinase ( Pf PanK) ( Saliba and Kirk, 2001 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the CoA-dependent fatty acid synthesis pathway is required for survival of liver stage parasites [26,27], inhibitors of CoA biosynthesis (pending the ability to permeate liver cells) are anticipated to be active against liver stage parasites. Fletcher et al [28] have identified compounds structurally distinct from pantothenate analogues that inhibit growth of P. falciparum via an effect on CoA biosynthesis. Some of these molecules also inhibit early and late stage gametocytes, suggesting that other molecules that target CoA biosynthesis might also be effective against these forms of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…For further structure-guided optimization of this compound class, it will be necessary to identify which of the enzymes involved in CoA synthesis constitutes the eventual target. A recent study using the same rescue approach used here, but with additional CoA pathway intermediates found that addition of pantethine, dephospho CoA and CoA all rescued the activity of Amb180780 to more than 75%, pointing at the enzymes phosphopantothenoylcysteine synthetase or phosphopantothenoylcysteine decarboxylase as the putative targets for Amb180780 [ 29 ]. For similar studies aiming at corroborating the putative targets of the new compound class presented here, the readily soluble and potent inhibitor KuWei173 ( 8e ) is now available.…”
Section: Discussionmentioning
confidence: 99%